Behavioral characterization of triple-hit schizophrenia-like Lisket rats derived from the Long Evans strain through acute and chronic behavioral tests - Zoldi, Anna; Kormoczi, László; Plesz, Szonja B.; Adlan, Leatitia G.; Kekesi, Gabriella; Liszli, Péter; Nyúl, Laszló G.; Braunitzer, Gábor; Horvath, Gyöngyi (Frontiers in Psychiatry, 2025)
BackgroundAutomated homecage systems provide valuable insights into rodent behavior in an undisturbed environment over extended periods. This study aims to identify behavioral differences between Long Evans (LE) rats (control) and a novel triple-hit schizophrenia model (Lisket), developed through selective breeding based on schizophrenia-related behavioral alterations following juvenile social isolation and ketamine treatment.MethodsPain sensitivity (tail-flick test), behavioral activity, and cognitive function were assessed in acute tests (Ambitus test) and chronic conditions (HomeManner system with a delay discount paradigm).ResultsLisket rats exhibited significantly decreased pain sensitivity, reduced locomotion and exploration, and impaired learning ability. While all LE rats learned to prefer the large-dose reward tray, only 69% of Lisket rats demonstrated this preference. Although Lisket rats displayed significant cognitive deficits, particularly under delay conditions, no clear signs of heightened impulsivity were detected. Personalized analysis revealed substantial interindividual variability in both groups, accompanied by high intraindividual fluctuations across different parameters.ConclusionsThis study provides the first comprehensive behavioral characterization of the Lisket model, a triple-hit schizophrenia-like rat strain derived from Long Evans rats, under both acute and chronic testing conditions. The automated, experimenter-free approach used in this study offers a promising tool for complex behavioral assessment. Furthermore, the findings emphasize the importance of individualized behavioral analysis alongside group-level assessments to enhance the translational validity of preclinical neuropsychiatric research.